Transformasi Ilmu Hayati melalui Pendekatan Bioteknologi Modern - Marsahip Marsahip (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of modern biotechnology has brought fundamental changes to the life sciences through the application of molecular biology, genetic engineering, and bioinformatics techniques. This article aims to examine the transformation of life sciences through modern biotechnology approaches and its impact on health, agriculture, the environment, and industry. The method used is a descriptive-analytical literature review based on international journal sources and relevant scientific publications. The results of the study indicate that technologies such as CRISPR-Cas9 enable precise gene editing for genetic disease therapy, while the mRNA vaccine platforms developed by Pfizer and Moderna demonstrate the acceleration of biomedical innovation in response to the global pandemic. In the agricultural sector, genetic engineering increases crop productivity and resilience, while in the environmental sector, biotechnology supports environmentally friendly bioremediation processes. However, ethical and regulatory challenges remain important concerns in its implementation. In conclusion, modern biotechnology plays a key role as a catalyst for sustainable, innovation-driven transformation in the life sciences.